Towards Accurate Predictions of Proton NMR Spectroscopic Parameters in Molecular Solids - Dračínský, Martin; Vícha, Jan; Bártová, Kateřina; Hodgkinson, Paul (Chemphyschem, 2020)
The factors contributing to the accuracy of quantum-chemical calculations for the prediction of proton NMR chemical shifts in molecular solids are systematically investigated. Proton chemical shifts of six solid amino acids with hydrogen atoms in various bonding environments (CH, CH2 , CH3 , OH, SH and NH3 ) were determined experimentally using ultra-fast magic-angle spinning and proton-detected 2D NMR experiments. The standard DFT method commonly used for the calculations of NMR parameters of solids is shown to provide chemical shifts that deviate from experiment by up to 1.5 ppm. The effects of the computational level (hybrid DFT functional, coupled-cluster calculation, inclusion of relativistic spin-orbit coupling) are thoroughly discussed. The effect of molecular dynamics and nuclear quantum effects are investigated using path-integral molecular dynamics (PIMD) simulations. It is demonstrated that the accuracy of the calculated proton chemical shifts is significantly better when these effects are included in the calculations.
Keywords: amino acids; molecular dynamics; solid state; density functional calculations; NMR spectroscopy